Providing external feedback and prompting the generation of internal feedback fosters achievement, strategies and motivation in concept learning. (December 2022) - Narciss, Susanne; Prescher, Claudia; Khalifah, Lugain; Körndle, Hermann
Abstract: The Interactive Two Feedback Loops Model (Narciss, 2008, 2013) suggests that not only providing external feedback but also prompting students to generate internal feedback may influence learning and motivation. This study aims at investigating the effects of internal and external feedback on achievement, strategy, and motivation in concept learning. Using a 2 × 3 experimental design with 121 teacher students we investigated the effects of combining internal feedback (i.e. self-explaining why a task solution is correct or incorrect) with three types of external feedback (no feedback; knowledge of result (KR); KR + knowledge about mistakes (KM)). Combining internal and external types of feedback was more beneficial for concept learning achievement, strategy use, as well as students' intrinsic motivation, and perceived competence, than providing either internal or external feedback. Most notably, if students are asked to generate internal feedback in terms of self-explaining their responses, simple external KR feedback is as beneficial as elaborated KM-feedback. Highlights: External feedback and prompting students to generate internal feedback may influence learning and motivation. Combining external and internal types of feedback is more beneficial than providing either external or internal feedback. Simple feedback can have similar benefits as elaborated feedback if combined with the generation of internal feedback.